2015
DOI: 10.1111/pace.12631
|View full text |Cite|
|
Sign up to set email alerts
|

Long‐Term Results of Cardiac Resynchronization Therapy: A Comparison between CRT‐Pacemakers versus Primary Prophylactic CRT‐Defibrillators

Abstract: In CRT treatment outside of the clinical trial setting, CRT-D treatment was not an independent predictor of long-term survival. Future research should focus on correct selection of the patients who receive enough benefit of an added defibrillator to justify CRT-D implantation instead of CRT-P treatment only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…A large multinational comparison of CRT‐D and CRT‐P implant rates reveal that among the 10 countries with the highest per capita rates of CRT implantation, CRT‐P devices range from 17% (Italy) to 49% (Hungary) of CRT devices 30. In the Swedish heart failure registry,31 63% of patients receiving CRT were implanted with CRT‐P 32. Our data accord with a smaller, single‐center study from the Cleveland Clinic, which demonstrated that among Class III/IV heart failure patients receiving CRT, 95% received CRT‐D versus CRT‐P 33.…”
Section: Discussionmentioning
confidence: 99%
“…A large multinational comparison of CRT‐D and CRT‐P implant rates reveal that among the 10 countries with the highest per capita rates of CRT implantation, CRT‐P devices range from 17% (Italy) to 49% (Hungary) of CRT devices 30. In the Swedish heart failure registry,31 63% of patients receiving CRT were implanted with CRT‐P 32. Our data accord with a smaller, single‐center study from the Cleveland Clinic, which demonstrated that among Class III/IV heart failure patients receiving CRT, 95% received CRT‐D versus CRT‐P 33.…”
Section: Discussionmentioning
confidence: 99%
“…Patients receiving CRT-D had a mean age in their 60s in all studies, while the mean age of CRT-P patients was in their 70s in eight studies 3,14,27,30,33,37,38,50 . Overall, those receiving CRT-D were younger (65 years vs. 68.2) , more often males (80.3% vs. 72%), had lower NYHA class (60% in NYHA class 2 vs. 88.6%), lower prevalence of atrial fibrillation (21% vs.…”
Section: Search Results and Patients' Characteristicsmentioning
confidence: 99%
“…Two-hundred and thirtyseven were retrieved for analysis of titles and abstracts and 49 of these were selected for further analysis of the full-length article. Eighteen were considered eligible for inclusion 3,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] .…”
Section: Search Results and Patients' Characteristicsmentioning
confidence: 99%
“…The remaining 5307 patients represent the study group—4037 (76.1%) received CRT-D (all primary prevention), while the remaining 1270 (23.9%) received CRT-P. Most patients from our cohort have been included and described in more detail in previous studies 5 6 8 9. Ischaemic cardiomyopathy was defined as the presence of systolic dysfunction associated with a history of myocardial infarction and/or the presence of significant coronary artery disease documented on a coronary angiogram.…”
Section: Methodsmentioning
confidence: 99%